Pemberdayaan Guru SMK dalam Pendidikan Pajak: Pelatihan Pemahaman Bentuk Usaha Tetap dan Pasal 26 - Y Agus Bagus Budi N; Triyanto; Aurora Rizky Andira (PT. Cendekia Sapta Indonesia, 2025)
This community service program aimed to improve vocational high school teachers’ understanding of taxation, particularly regarding Permanent Establishment (Bentuk Usaha Tetap) and Article 26 provisions. The main problem addressed was the low level of tax literacy among teachers, which has hindered the effective delivery of tax education in schools and limited students’ awareness of the importance of taxes from an early age. The program was implemented through participatory training methods, including interactive lectures, group discussions, and case studies, attended by 20 vocational high school teachers in West Jakarta. Evaluation was carried out using pre-test and post-test assessments to measure knowledge improvement, as well as satisfaction questionnaires to evaluate the training methods. The results showed a significant improvement, with the average score increasing from 62.5 (pre-test) to 86.3 (post-test), and most participants (82%) rated the training methods as highly effective. This program not only enhanced teachers’ competence and confidence in teaching tax materials but also contributed to fostering a tax-conscious culture within schools. In the long term, this initiative can be replicated in other schools to help shape a tax-compliant and responsible younger generation.